Factor influencing the behavioral intention for smart farming (drone) application among oil palm smallholders. - Madlaim, Nur Izatul Nadhirah; Kamarul Zaman , Nur Badriyah (Journal of Islamic, Social, Economics and Development, 2025)
Smart farming in plantations brings numerous benefits to agricultural practices especially among smallholders in oil palm plantation. By leveraging advanced technologies like drones farmers can enhance efficiency in operation and optimize crop production. The limited adoption of drones among smallholders in agriculture is mainly due to financial constraints and lack of knowledge and skills. The study aims to determine factors that impact the behavioral intention of adopting smart farming technology (drone) among oil palm smallholders in Johor, Malaysia. This study used the Unified Theory of Acceptance and Use of Technology (UTAUT) as the conceptual foundation in developing the conceptual framework. The quantitative research method had been employed, and data had been collected through a structured questionnaire that had been distributed to 256 oil palm smallholders in Johor using convenience sampling technique. The data had been analyzed using the Statistical Package for Social Science (SPSS) software, and descriptive analysis and multiple regression analysis had been conducted to determine the relationship between the independent variables (performance expectancy, effort expectancy, social influence, and facilitating conditions) and the dependent variable (behavioral intention to adopt smart farming technology). The findings of this study would provide insights into the current level of adoption and the factors influencing the acceptance of smart farming technology (drone) among oil palm smallholders in Johor. This study can also be used as reference material for policy maker, government, and industry.